Anterior cervical surgery to treat diffuse idiopathic skeletal hypertrophic combined with cervical disc herniation: A case report. Issue 22 (4th June 2021) - Gao, Kun; Cao, Yafei; Liu, Weidong; Sun, Shufen; Wu, Yihong; Yu, Weiji
Abstract: Rationale: Diffuse idiopathic skeletal hyperostosis (DISH) is a skeletal disease characterized by calcification of anterolateral ligaments of the spine and the rest of the body. DISH combined with disc herniation induces complex symptoms and is more difficult to treat. Here, we describe a complicated case of a patient diagnosed with DISH as well as cervical disc herniation that was successfully treated using anterior cervical surgery. Patients concern: A 69-year-old Asian male experienced dysphagia and weakness in his left limbs. He also experienced a stiff neck and right slant over a 6-month period. Diagnosis: An X-ray revealed calcification of the C4-7 vertebral front edge and a narrowed intervertebral space between C5/6. Coronal and sagittal computerized tomography (CT) and magnetic resonance imaging (MRI) both showed compression of the spinal cord at the cervical 5/6. Esophagography revealed that osteophytes in the anterior margin of vertebral body (C4-C7) oppressed the esophagus. Interventions: An operation focused on anterior cervical C5/6 disc fusion and anterior vertebral C4-7 osteophyte removal was performed. Outcomes: After the operation, X-ray and CT showed that most osteophytes were removed and spinal cord compression was relieved. One day following the operation, both dysphagia and numbness in limbs were improved. Strong recovery was observed at the three-month follow-up exam. Lessons: This complex DISH combined with disc herniation case is rarely observed in patients. Anterior cervical disc fusion and anterior vertebral osteophyte removal were effective treatment measures. This case study provides insight into treating cases presented with cervical spine complications associated with DISH combined with other ailments.